EFFECT OF PUBLIC FINANCIAL MANAGEMENT REFORM ON FINANCIAL OPERATIONS: THE CASE OF MINISTRY OF FINANCE IN PUNTLAND STATE OF SOMALIA. - Moulid Abdirahman Ali (My University, 2022)
The PFMRs seek to address gaps identified in the devolved systems of government and public organizations to remedy inadequate strategy orientation and lapsed strategy as well as to build on institutional transformation. The purpose of this study to investigate the effects of public financial management reforms on financial operations in the Ministry of Finance of Puntland State.. To achieve this purpose the researcher was formulated research objectives. This study adopted a descriptive survey design and multiple regression analysis where the population comprised of 120 respondents at the Ministry of finance headquarter. The researcher used primary and secondary sources to collect the data through the use of a questionnaire, which comprised of close-ended questions. The sample of this study was 92 who had taken from the target population for the survey.The study was guided by three objectives; To examine the effect of Political Commitment on financial operation, To examine the effect technical capacity of staff on financial operation and To examine the effect Donor support on financial operation in the ministry of finance in Puntland state, Somalia.The study found that Poor political commitment and lack of sufficient technical capacity were the most prevalent hindrances in the implementation of public financial management reforms. The study concludes that the role of donors support had significant effect on PFM reform. Despite the fact that donors were not fully funded the PFM reforms to implement successfully. The study recommended that the Puntland government have to create strong political commitment, should improve and adopt appropriate technical capacity enhancement to ensure the quality, reliability to achieve the implementation of PFM reform. Puntland State should allocate budget and special departments for the implementation of PFM reform to ensure the sustainability of the program. Keywords: Public financial management, Political Commitment, Technical Capacity, and Donors support.